Introduction of a hybrid treatment delivery system used for quality assurance in multi-catheter interstitial brachytherapy. (2nd May 2018) - Kallis, Karoline; Kreppner, Stephan; Lotter, Michael; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph
Abstract: Multi-catheter interstitial brachytherapy (iBT) is a treatment option for breast cancer patients after breast conserving surgery. Typically, only a few additional quality interventions after the first irradiation have been introduced to ensure the planned treatment delivery. Therefore, the purpose of this study is to show the possibilities of an electromagnetic tracking (EMT) system integrated into the afterloader for quality assurance (QA) in high-dose rate (HDR) iBT of patients with breast cancer. The hybrid afterloader system equipped with an electromagnetic sensor was used for all phantom and patient measurements. Phantom measurements were conducted to estimate the quality of different evaluation schemes. After a coherent point drift registration of the EMT traces to the reconstructed catheters based on computed tomograms the dwell positions (DP) were defined. Different fitting and interpolation methods were analyzed for the reconstruction of DPs. All estimated DPs were compared to the DPs defined in treatment planning. Until now, the implant geometry of 20 patients treated with HDR brachytherapy was acquired and explored. Regarding the reconstruction techniques, both fitting and interpolation were able to detect manually introduced shifts and swaps. Nonetheless, interpolation showed superior results (RMSE = 1.27 mm), whereas fitting seemed to be more stable to distortion and motion. The EMT system proved to be beneficial for QA in brachytherapy and furthermore, clinical feasibility was proven.